PENGARUH KEMIRINGAN STRAIGHT BLADE TERHADAP PENINGKATAN KEMAMPUAN SELF-STARTING TURBIN HIDROKINETIK ARTICULATING H-ROTOR - Desy Rianti; Dwi Anung Nindito; Raden Haryo Saputra (Teknika, 2021)
The Articulating of H-Rotor is a development of the turbine from H-Darrieus which has a straight blade tilted with the aim of correcting poor self-starting due to the dominance of lift force. How likely is the influence of straight blade slope on turbine performance and it is important to be examined. The aim of this study was to find out the effect of the straight blade slope of the Articulating H-Rotor turbine to increase the self-starting ability. Hydrokinetic turbine experimental test method was carried out in a water channel (flume) using 3 NACA 0018 profile blades with varying inclination angles of 0o (vertical blade), 30o (inflated blade) and -30o (cupped blade). The result indicated that the Articulating H-Rotor hydrokinetic turbine with a blade slope of 0o had a larger RPM value and it was more dominant in working with lift force. The Articulating H-Rotor hydrokinetic turbine with a blade tilted of 30o provides higher torque and increases drag, increasing self-starting for rotation. The shape of the turbine frontal area with a blade slope of 30o was better able to respond the kinetic energy that raised from the flow velocity distribution profile of the water flow. The results of this study can contribute to the design of the tilted blade H-Darrieus turbine.